2021
DOI: 10.1177/11033088211025949
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s Been a Massive Struggle’: Exploring the Experiences of Young People Leaving Care During COVID-19

Abstract: This article explores the experiences of young people leaving state care during COVID-19. Twenty-one young people, predominantly from Wales, engaged in semi-structured interviews and/or contributed poems and artwork conveying their experiences of the pandemic. The data generated offered insights into young people’s daily lives, including their routines and relationships, as well as access to resources and services. The study found stark disparity in young people’s experiences, with some reassured by support re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 43 publications
4
47
0
Order By: Relevance
“…Some of the young adults with a history of maltreatment emphasized their complex relationships with their families and the influence it had on them mentally. Feeling of safety and belonging were also found among other groups of vulnerable young adults during COVID‐19 who felt that being confined to their ‘unsafe’ home amplified their anxieties (Roberts, Mannay, et al, 2021 ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Some of the young adults with a history of maltreatment emphasized their complex relationships with their families and the influence it had on them mentally. Feeling of safety and belonging were also found among other groups of vulnerable young adults during COVID‐19 who felt that being confined to their ‘unsafe’ home amplified their anxieties (Roberts, Mannay, et al, 2021 ).…”
Section: Discussionmentioning
confidence: 86%
“…Similar challenges were document among other vulnerable group of young people. For example, Roberts, Mannay et al ( 2021 ) found that during COVID‐19, care leavers faced increased challenges compounded by diminished service availability and individual ability to influence their situations including access to basic provisions, being able to sustain the costs of daily living, residing in inappropriate accommodation and struggling with the absence of both practical and emotional support. While some young people felt supported, others felt neglected and forgotten Roberts, Rees et al ( 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A group that received little attention, but was hit particularly hard by the pandemic, was young people living on the streets (Gewirtz O'Brien et al 2021). Another similarly affected group were those who left state care during the pandemic (Roberts et al 2021). The transition to adulthood is difficult for care leavers even without a pandemic.…”
Section: Being Young In Times Of a Pandemicmentioning
confidence: 99%
“…Though not yet fully understood, the longer-term consequences of pandemic restrictions upon CYP are anticipated to cluster broadly around mental health, social connections, and disruptions to education and employment ( Dewa et al, 2021 ; McKinlay et al, 2022 ; Scott et al, 2021 ), with data from earlier stages of the pandemic indicative of an emerging mental health crisis for CYP ( Cielo et al, 2021 ; Huang & Ougrin, 2021 ; Varma et al, 2021 ). Meanwhile, whilst some CYP have highlighted positive experiences and outcomes in comparison to their pre-pandemic life (such as more time spent with family or the opportunity for a slower pace of life), many groups of CYP remain less likely to bounce back as restrictions have eased, particularly those experiencing marginalisation or disadvantage ( Couch et al, 2021 ; Creswell et al, 2021 ; Roberts et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%